Peningkatan Kualitas Proses Pembelajaran Melalui Lesson Study - Rusli (Jurnal Alasma : Media Informasi dan Komunikasi Ilmiah, 2021)
Lesson study is a case analysis method in learning practice, aimed at assisting the professional development of teachers and opening up opportunities for them to learn from each other based on real practices in the classroom. Lesson Study is not a strategy or method in learning, but is one of the coaching efforts to improve the learning process carried out by a group of teachers collaboratively and continuously, in planning, implementing, observing and reporting learning outcomes. The form is a joint task or collaboration between teachers in the same field of study (a consortium in the field of study). Learning planning is discussed together, there is a teacher who is used as a model. The teacher who is used as this model carries out learning in the classroom, other teachers (as observers) observe student learning responses until the teaching and learning activities are finished. After that, a discussion was held between the observer and the model teacher about the learning process carried out by the model teacher. The results of the discussion for the improvement/enrichment of the next learning. Lesson study aims firstly to gain a better understanding of how students learn and teachers teach, secondly, to obtain certain results that can be utilized by other teachers outside of lesson study participants, thirdly, to improve learning systematically through collaborative inquiry, and fourthly to build a pedagogical knowledge, where a teacher can draw knowledge from other teachers.